Models of game intelligence and creativity in sport: Implications for skill acquisition - Memmert, D.; König, S. (Skill acquisition in sport: research, theory and practice, 2020)
Decision-making encompasses the prerequisites for performance in sport, which are required for the quick and appropriate solution of tasks. In this respect, it plays a central role in sports games and combat sports in particular. Decision-making, understood as the selection and solution of tasks, must be delimited from strategy that refers to longer-term, coaching-related aspects. Decision-making is differentiated into a practical and methodical perspective of training in defense and attack tactics on the one hand, and in individual, group, and team tactics on the other hand as it could be shown in the initial section of this chapter. Decision-making, from a sports science perspective, has led to the development of several models which describe, explain and predict decision-making. Like other sporting performance factors, there are different approaches to teaching decision-making skills, which can be broadly described as implicit or explicit. Based on these tactical teaching approaches different authors have developed implications for the acquisition of open skills, which are dominant in game and combat sports. The most powerful are subsumed under the concepts of skill variation and skill selection. Finally, there are specific diagnostic instruments for evaluating tactical intelligence and tactical creativity, of which the game test situation might be the most valid with respect to balancing external and internal validity. The following recommendations for skill acquisition within the framework of decision-making can be made: ° The primacy of tactical awareness should always be considered when teaching open skills that is, an approach which focuses on the solution of tactical problems must be aimed for. Such a tactical approach should be offered on various levels of complexity to arrange appropriate game forms for the learners ° Within the tactical approach, skill acquisition and skill execution should be taught using varying drills or games, which include descision making